Uranium dioxide pellet and preparation method thereof

By adding metal oxides and uranium octoxide to the uranium dioxide core pellet, combined with staged mixing and multiple pressing processes, the problem of cladding damage caused by stress at high temperatures is solved, and the core pellet is improved The high-temperature plastic deformation capability enhances the flexible operation and high-fuel power generation capacity of nuclear power plants.

CN119296823APending Publication Date: 2025-01-10CHINA NUCLEAR POWER TECH RES INST CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411579905.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing nuclear fuel pellets are damaged by stress caused by the cladding-core interaction (PCI) effect at high temperatures, limiting the flexible operation and high fuel consumption power generation capacity of nuclear power plants, and the pellet composition and preparation process lead to The size of the grain is too large, resulting in weakening of creep ability.

Method used

Uranium dioxide core pellets consisting of pore-forming agent, lubricant, metal oxide additive A and tri-uranium octadecanoic additive B are used to control grain size and defect type through staged mixing and multiple pressing processes to improve the core pellet size. high temperature plastic deformation capability.

Benefits of technology

It effectively alleviates fuel damage caused by the PCI effect, improves the high-temperature plastic deformation capability of the core pellet, reduces the risk of fuel failure, and reduces the production cost and quality control difficulty.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119296823A_ABST
    Figure CN119296823A_ABST
Patent Text Reader

Abstract

The invention discloses a uranium dioxide pellet and a preparation method thereof. The uranium dioxide pellet is prepared from the following raw materials in percentage by mass: 0.1-0.3 wt% of a pore forming agent, 0.1-0.3 wt% of a lubricant, 0.03-0.15 wt% of an additive A, 12-15 wt% of an additive B and the balance of uranium dioxide, the additive A comprises at least one metal oxide, metal elements in the metal oxide are IVB group, VB group, VIB group or VIIB group elements, and the additive B is triuranium octaoxide; the preparation method comprises the following steps: S1, mixing: mixing the pore-forming agent, the additive A, the additive B and uranium dioxide; s2, granulating: pressing for the first time, sieving with a screen, and then adding a lubricant for mixing; s3, forming, wherein secondary pressing is conducted; and S4, sintering: sintering the green body in a certain sintering atmosphere at a certain sintering temperature. According to the method, the situation that the average grain size of the uranium dioxide pellet is too large is avoided, the high-temperature plastic deformation capacity of the uranium dioxide pellet is improved, and the fuel failure risk caused by the PCI effect can be effectively reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nuclear fuel pellets, and in particular to a uranium dioxide pellet and a preparation method thereof. Background Art

[0002] Nuclear fuel pellets are the most important components in nuclear reactors and are related to the economic and safe operation of nuclear reactors. Nuclear fuel pellets are encapsulated in zirconium alloy cladding tubes, which provide a place for nuclear fission reactions. During the service in the reactor, the fuel rod cladding will come into contact with each other due to the creep of the cladding and the swelling of the pellets, thereby generating tensile stress on the inner wall of the cladding. This stress between the pellets and the cladding is called cladding-pellet interaction (PCI). Severe PCI effects may cause the cladding to break, resulting in leakage of radioactive fission gas. Under high burnup conditions, for transients where the power-temperature increases sharply in a short period of time, the pellets will apply greater stress to the cladding due to thermal expansion, which may cause the cladding to break. The PCI effect is the main mechanism that causes fuel rod damage and is also an important safety criterion for reference in fuel design. The significant PCI effect limits the flexible operation capability and high-burnup power generation capability of nuclear power plants, and restricts the continuous improvement of the economic benefits of nuclear power.

[0003] The existing pellet preparation method adds a mixture of Al2O3 (aluminum oxide) and SiO2 (silicon dioxide) to UO2 (uranium dioxide) powder, so that it generates a liquid phase of aluminosilicate glass at about 1600°C, which infiltrates and disperses at the UO2 grain boundaries, and uses the property of glass gradually softening as the temperature rises to enhance the UO2 grain boundary sliding deformation ability at high temperatures. However, this method introduces a second phase that cannot be dissolved in the solid into the pellet, turning the pellet from a pure substance into a composite, which puts higher requirements on the performance and production of the pellet product. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a uranium dioxide pellet and a preparation method thereof.

[0005] The technical solution adopted by the present invention to solve the technical problem is: a uranium dioxide pellet is made of the following raw materials in percentage by weight: 0.1-0.3wt% of a pore former, 0.1-0.3wt% of a lubricant, 0.03-0.15wt% of an additive A, 12-15wt% of an additive B, and the balance is uranium dioxide; the additive A comprises at least one metal oxide, the metal element in the metal oxide is an element of group IVB, group VB, group VIB or group VIIB, and the additive B is triuranium octoxide.

[0006] In some embodiments, the pore former is ammonium oxalate; and / or, the lubricant is acryl wax or stearate.

[0007] In some embodiments, the cation radius of the metal element in the metal oxide is greater than4+ The radius of the ion is at least 30% smaller, and the equivalent boron content of the metal element is less than 0.004 μg / gU.

[0008] A method for preparing the above-mentioned uranium dioxide pellets comprises the following steps:

[0009] S1, mixing: using pore former, lubricant, additive A, additive B and uranium dioxide as raw materials, mixing the pore former, additive A, additive B and uranium dioxide to obtain a first mixture; the mass percentages of the raw materials satisfy: pore former 0.1-0.3wt%, lubricant 0.1-0.3wt%, additive A 0.03-0.15wt%, additive B 12-15wt%, and the balance is uranium dioxide;

[0010] S2, granulation: the first mixture is compressed for the first time and sieved with a sieve, and then a lubricant is added and mixed to obtain a second mixture;

[0011] S3, molding: pressing the second mixture for a second time to obtain a green body;

[0012] S4. Sintering: Sinter the green body in a certain sintering atmosphere and sintering temperature to obtain uranium dioxide pellets.

[0013] In some embodiments, step S1 includes the following sub-steps:

[0014] S1.1, first stage mixing: mixing the pore former, additive A, additive B and uranium dioxide for 10 to 13 mixing cycles to obtain a first premixed powder;

[0015] S1.2, two-stage mixing: the first premixed powder is mixed for 25 to 30 mixing cycles to obtain a first mixture.

[0016] In some embodiments, step S1 includes the following sub-steps:

[0017] S1.3, premixing: uranium dioxide is added twice, and part of the uranium dioxide and additive A are mixed for a total of 25 to 30 mixing cycles to obtain a second premixed powder;

[0018] S1.4, main mixing: the second premixed powder, additive B, the remaining uranium dioxide and the pore-forming agent are mixed for a total of 25 to 30 mixing cycles to obtain a first mixture.

[0019] In some embodiments, step S1 includes the following sub-steps:

[0020] S1.5, premixing: Additive B is added twice, and additive A and part of additive B are mixed for a total of 25 to 30 mixing cycles to obtain a third premixed powder;

[0021] S1.6, main mixing: the third premixed powder, the remaining part of the additive B, uranium dioxide and the pore-forming agent are mixed for 3 to 5 mixing cycles to obtain a first mixed powder; alternatively, the third premixed powder is added in multiple times, firstly, part of the third premixed powder, the remaining part of the additive B, uranium dioxide and the pore-forming agent are mixed for 3 to 5 mixing cycles, then part of the third premixed powder is added and mixed for 3 to 5 mixing cycles, and part of the third premixed powder is added and mixed repeatedly until all the third premixed powder is added, and then mixed for 3 to 5 mixing cycles to obtain a first mixed powder.

[0022] In some embodiments, in step S1, each mixing cycle includes mixing and cooling, the sum of the mixing time and the cooling time of each mixing cycle is ≤10 minutes, and the mixing speed is 50-200 r / min.

[0023] In some embodiments, in step S2, after the first mixture is pressed for the first time, the density is 4 to 6 g / cm 3 ; After sieving through a sieve, the first spheroidization is performed for 10 to 15 minutes, and then a lubricant is added and the second spheroidization is performed for 5 to 10 minutes. The aperture of the sieve is 1 to 2 mm;

[0024] In step S3, the pressing stress of the second pressing is 250-450 MPa, and the density of the green body is 5.5-6.5 g / cm 3 .

[0025] In some embodiments, in step S4, the sintering atmosphere is hydrogen containing up to 5 vol% water vapor or carbon dioxide containing at least 50 vol% nitrogen or argon, the gas flow rate of the sintering atmosphere is 150-250 L / min, the sintering temperature is 1500-1800°C, and the sintering time is 4-12 hours.

[0026] Beneficial effects of the present invention:

[0027] The present invention adds a small amount of additive A and additive B, i.e., metal oxides, to uranium dioxide, thereby avoiding the formation of a second phase in the pellet due to excessive use of the additives. The defect type and concentration in the crystal lattice of the UO2 pellet are changed by the metal oxides, so that the UO2 pellet has stronger material fluidity at high temperature and better plastic deformation ability, and can relieve the stress generated when the UO2 pellet contacts the cladding, thereby reducing the fuel damage caused by the mechanical interaction between the cladding and the pellet.

[0028] The uranium dioxide pellet preparation method of the present invention avoids the weakening of the creep capacity of the pellet caused by the excessive average grain size of the pellet due to the pellet composition and preparation process, improves the high-temperature plastic deformation capacity of the uranium dioxide pellet, and can effectively reduce the risk of fuel failure caused by the PCI effect. The production cost, preparation process and quality control of the present invention are equivalent to those of commercial UO2 pellets, and the preparation method of the present invention can be used for laboratory preparation or industrial-grade manufacturing of uranium dioxide pellets of 1 kg / batch to 500 kg / batch. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The present invention will be further described below with reference to the accompanying drawings and embodiments, in which:

[0030] Figure 1 is an electron microscope image of the uranium dioxide pellet of Example 1 of the present invention at high temperature;

[0031] Figure 2 This is an electron microscope image of a commercial uranium dioxide pellet at high temperature;

[0032] Figure 3 is an electron microscope image of the uranium dioxide pellets of Example 1 of the present invention after power transient;

[0033] Figure 4 This is an electron microscope image of a commercial uranium dioxide pellet after a power transient. DETAILED DESCRIPTION

[0034] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the present invention will be further described in detail below in conjunction with embodiments. The embodiments are only used to explain the present invention and do not constitute a limitation on the protection scope of the present invention.

[0035] The present invention provides a uranium dioxide pellet, which is made of the following raw materials in mass percentage: 0.1-0.3wt% of pore former, 0.1-0.3wt% of lubricant, 0.03-0.15wt% of additive A, 12-15wt% of additive B, and the balance is uranium dioxide. Among them, the mass percentage of the pore former can be selected from 0.1wt%, 0.15wt%, 0.2wt%, 0.25wt%, 0.3wt%, etc., the mass percentage of the lubricant can be selected from 0.1wt%, 0.15wt%, 0.2wt%, 0.25wt%, 0.3wt%, etc., the mass percentage of the additive A can be selected from 0.03wt%, 0.05wt%, 0.1wt%, 0.12wt%, 0.15wt%, etc., and the mass percentage of the additive B can be selected from 12wt%, 13wt%, 13.5wt%, 14wt%, 15wt%, etc.

[0036] The additive A comprises at least one metal oxide, wherein the metal element in the metal oxide is an element of group IVB, group VB, group VIB or group VIIB, and these metal elements have variable valence. The cation radius of the metal element in the metal oxide is related to the valence state. The higher the valence state of the metal element, the smaller the cation radius. Preferably, the cation radius is greater than U 4+ The radius of the ion (0.097nm) is at least 30% smaller, making it easier for the cation of the metal element to enter the interstitial position of the UO2 lattice. The equivalent boron content of the metal element is less than 0.004μg / gU. Preferably, the metal element can be chromium (Cr), titanium (Ti), manganese (Mn), and vanadium (V). Additive A can generate a large number of interstitial ion defects with positive charge valence states, which increases the concentration of U ion vacancies due to the principle of electrical neutrality, increases the diffusion coefficient of UO2, and thus improves the fluidity of the material.

[0037] Additive B is uranium trioxide (U3O8), which has the following main functions: 1) to recycle waste materials in the pellet preparation process; 2) to adjust the proportion of small pores in the pellet; 3) to provide more U3O8 5+ ions, promoting the densification and sintering of the core block at a lower temperature.

[0038] The pore forming agent is used to adjust the macropore ratio in the core block, and the pore forming agent is preferably ammonium oxalate. The lubricant is used to optimize the pressing performance of the green body during the core block preparation process, and the lubricant is preferably a ke wax or stearate, and the stearate can be zinc stearate, lithium stearate or calcium stearate.

[0039] The present invention changes the defect type and concentration in the UO2 crystal by adding metal oxides (including additive A and additive B), and the principle is as follows.

[0040] According to the knowledge of material thermodynamics, the main defects in solid lattices are Schottky defects and Frankel defects. The defect equation formed by Schottky defects is:

[0041]

[0042] In the formula, null represents a defect-free state, V o is an oxygen vacancy, V U In the formula of the present invention, * represents a positive charge, and ' represents a negative charge.

[0043] The defect reaction equilibrium constant of Schottky defect is K s , the expression is as follows:

[0044] K s =[V O ** ] 2 [V U″″]=exp(-ΔG S / kT) (2)

[0045] In the formula, [V U ] is the uranium vacancy concentration, [V O ] is the oxygen vacancy concentration, ΔG S is the change in Gibbs free energy, k is the Boltzmann constant, and T is the Kelvin temperature.

[0046] Since the volume of oxygen ions is smaller than that of uranium ions, oxygen ions can enter the interstitial position of the UO2 lattice. The Frankl defect formation equation of oxygen ions is expressed as follows:

[0047]

[0048] In the formula, O O represents the oxygen atom at the normal lattice site, O i is an interstitial oxygen defect, V O is an oxygen vacancy. The defect reaction equilibrium constant of the Frankel defect is K Fo , the expression is as follows:

[0049] K Fo =[O″ i ][V O **] / [O O ]=exp(-ΔG Fo / kT) (4)

[0050] In the formula, [O i ] is the interstitial oxygen defect concentration, [V O ] is the oxygen vacancy concentration, [O O ] is the concentration of oxygen atoms at normal lattice sites, ΔG Fo is the Frankel defect formation energy of oxygen atom, k is the Boltzmann constant, and T is the Kelvin temperature.

[0051] The diffusion coefficient of uranium ions is D U , the expression is as follows:

[0052] D U =D V [V U ] (5)

[0053] Where D V is the vacancy self-diffusion coefficient, which is 2.34×10 -6 ,[V U ] is the uranium vacancy concentration.

[0054] The diffusion coefficient of oxygen ions is D O , the expression is as follows:

[0055] D O =D V [V O ] (6)

[0056] Where D V is the vacancy self-diffusion coefficient, which is 2.34×10 -6 ,[V O ] is the oxygen vacancy concentration.

[0057] From the above equation, we can know that at a certain temperature, the interstitial oxygen defect concentration [O i ], oxygen vacancy concentration [V O ], uranium vacancy concentration [V U ] are related to the activation energy of defect formation. If the temperature and activation energy remain unchanged, the vacancy concentration (i.e. [V U ] and [V O ]) is constant, and the diffusion coefficient is also constant.

[0058] To enhance the material flow of UO2 and improve its high temperature plasticity, the diffusion coefficient (D U or D O ), according to existing research conclusions, adding metal oxides to UO2 can change [V U ] and [V O ] to adjust the value of D U or D O , the specific relationship is as follows:

[0059] [V O ]=8 -1 *[(x 2 +64K1) 0.5 ±x] (7)

[0060] [V U ]=64K2*[(x 2 +64K1) 0.5 ±x] -2 (8)

[0061] In formula (7) and formula (8), x is the molar percentage of the added metal oxide, K1=exp(-3.5eV / kT), K2=exp(-6.5eV / kT), where eV is the unit of electron volt, k is the Boltzmann constant, and T is the Kelvin temperature. If the valence of the metal ion in the metal oxide is higher than +4, a minus sign is used, otherwise a plus sign is used.

[0062] Adding metal oxides that satisfy equations (7) and (8) to UO2 can theoretically increase the material diffusion rate of UO2 and enhance its plastic deformation ability. However, in actual experiments, it was found that the solid solubility, charge properties and position of metal oxide ions in the UO2 lattice will affect the vacancy defect concentration, especially [V U ] has a significant impact. U It is in a 4-valence state (originally there should be a uranium ion with a 4+ valence state at this position, and the vacancy will show a relative charge effect), so the introduction of a large number of positively charged defects can increase [V U ] to achieve electrical neutrality.

[0063] At high temperatures, the added metal oxide ions are driven into the interstitial sites of the UO2 lattice to become M i Defects, among which metal oxide ions with smaller radius are more likely to enter the interstitial sites of the UO2 lattice, and ions with 2+, 3+, 4+ and even higher valence states can achieve an increase in [V U ] goal. Generally speaking, the higher the positive valence, the more electrons the ion loses and the smaller the radius. However, a large amount of hydrogen is used in the sintering atmosphere of UO2 pellets, making it difficult for the ions to maintain a high positive valence at high temperatures. Therefore, the metal ions of the additive enter the UO2 lattice interstitial sites as much as possible at low temperatures with a higher positive valence (smaller ion radius) to form M i defects, and the metal ions are reduced to a stable positive valence state (usually 2+) at high temperature to achieve [V U ] is improved, becoming a feasible method to enhance the UO2 diffusion coefficient to improve the flow capacity of UO2 material.

[0064] The general expression of the steady-state creep rate ε of dense ceramics is:

[0065] ε = (b / d) q ×(σ / G) n ×A×D×(Gb / kT) (9)

[0066] In the formula, D is the diffusion coefficient, b is the Burgers vector, d is the average grain size, G is the shear modulus, σ is the compressive stress, q is the grain size index, n is the stress index, A is the fitting coefficient, k is the Boltzmann constant, and T is the Kelvin temperature. It can be seen that the creep rate ε is proportional to the diffusion coefficient and the compressive stress, but inversely proportional to the grain size.

[0067] The industry-recognized expression for the creep rate ε of UO2 pellets is:

[0068] ε = {[A1σexp(-Q1 / RT)] / [(A2+ρ)d 2 ]}+{[A3σ 4.5exp(-Q2 / RT)] / (A4+ρ)} (10)

[0069] In the formula, Q1 is the activation energy of point defect diffusion, Q2 is the activation energy of dislocation climb, ρ is the density, d is the average grain size, σ is the compressive stress, A1~A4 are fitting coefficients, R is the gas constant, and T is the Kelvin temperature. It can be seen that the creep rate ε is proportional to the compressive stress, but inversely proportional to the grain size.

[0070] Therefore, under the same temperature and compressive stress conditions, increasing the diffusion coefficient D will increase the creep rate ε of UO2 and improve the plastic deformation capacity of the pellets, thereby alleviating the force impact when the cladding and pellets are in mechanical contact and reducing the risk of damage to the fuel cladding. The average grain size d of the UO2 pellets should not be too large (the nominal value of d exceeds 50μm and the maximum value exceeds 60μm), but the nominal value of d should be controlled within the range of 8 to 50μm. Since the grain size is strongly related to factors such as sintering temperature, sintering atmosphere and additive content, and has a significant linear relationship, the grain size of the UO2 pellets can be more accurately controlled within a certain range by adjusting the temperature, atmosphere and additive content. Therefore, the sintering temperature and sintering time of the pellets should be appropriately reduced. In order to ensure a lower sintering temperature and a shorter time to make the density of the pellets reach about 95% TD (theoretical density), U3O8 is introduced by adding U3O8. 5+ The ions promote the shrinkage of the pellet volume to achieve pellet densification.

[0071] The present invention provides a UO2 pellet with appropriate plasticity at high temperature. By adding a trace amount of dopant, the defect type and concentration in the UO2 pellet lattice can be changed to make UO2 have stronger material fluidity and better deformation ability at high temperature, thereby alleviating fuel damage caused by the PCI effect. The UO2 pellet of the present invention can significantly improve the safety of nuclear power plants during flexible operation, improve the reliability of high fuel consumption operation, and make nuclear power more economically competitive in the energy market.

[0072] The present invention also provides a method for preparing the above-mentioned uranium dioxide pellets, comprising the following steps:

[0073] S1. Mixing: Using pore former, lubricant, additive A, additive B and uranium dioxide as raw materials, the pore former, additive A, additive B and uranium dioxide are mixed to obtain a first mixture. The mass percentages of the raw materials satisfy: pore former 0.1-0.3wt%, lubricant 0.1-0.3wt%, additive A 0.03-0.15wt%, additive B 12-15wt%, and the balance is uranium dioxide. The components of the pore former, lubricant, additive A, additive B and uranium dioxide are the same as those described above.

[0074] The mixing step is divided into three implementation modes:

[0075] In the first embodiment, preferably, the mass percentages of the raw materials satisfy: pore former 0.1-0.15wt%, lubricant 0.1-0.3wt%, additive A 0.05-0.15wt%, additive B 12-15wt%, and the remainder is uranium dioxide. Step S1 includes the following sub-steps:

[0076] S1.1, first stage mixing: pore former, additive A, additive B and uranium dioxide are mixed for 10 to 13 mixing cycles to obtain a first premixed powder. The number of mixing cycles can be 10, 11, 12, 13, etc., and a high-efficiency stirring mixer can be used for mixing.

[0077] S1.2, two-stage mixing: the first premixed powder is mixed for 25 to 30 mixing cycles to obtain a first mixture. The number of mixing cycles can be selected from 25, 26, 27, 28, 29, 30, etc., and a high-efficiency stirring mixer can be used for mixing.

[0078] In the second embodiment, preferably, the mass percentages of the raw materials satisfy: pore former 0.1-0.15wt%, lubricant 0.1-0.3wt%, additive A 0.03-0.06wt%, additive B 12-15wt%, and the remainder is uranium dioxide. Step S1 includes the following sub-steps:

[0079] S1.3, premixing: uranium dioxide is added twice, and part of the uranium dioxide and additive A are mixed for a total of 25 to 30 mixing cycles to obtain a second premixed powder. Among them, the mass percentage of part of the uranium dioxide to the total uranium dioxide is 17 to 33wt%, and 17wt%, 20wt%, 22wt%, 25wt%, 33wt%, etc. can be selected. The number of mixing cycles can be selected as 25, 26, 27, 28, 29, 30, etc., and a high-efficiency stirring mixer can be used for mixing.

[0080] S1.4, main mixing: mix the second premixed powder, additive B, the remaining uranium dioxide and the pore-forming agent for a total of 25 to 30 mixing cycles to obtain a first mixture. Among them, the number of mixing cycles can be selected from 25, 26, 27, 28, 29, 30, etc., and a high-efficiency stirring mixer or orbital spiral mixer can be used for mixing. In some embodiments, the second premixed powder can be added gradually in multiple times. Specifically, first mix part of the second premixed powder, additive B, the remaining uranium dioxide and the pore-forming agent, then add part of the second premixed powder for mixing, repeat adding part of the second premixed powder and mixing until all the second premixed powder is added, and then mix.

[0081] In the third embodiment, preferably, the mass percentages of the raw materials satisfy: pore former 0.1-0.15wt%, lubricant 0.1-0.3wt%, additive A 0.05-0.07wt%, additive B 12-15wt%, and the remainder is uranium dioxide. Step S1 includes the following sub-steps:

[0082] S1.5, premixing: Additive B is added twice, and additive A and part of additive B are mixed for a total of 25 to 30 mixing cycles to obtain a third premixed powder. Among them, the mass percentage of part of the additive to the raw material is 4 to 7wt%, and 4wt%, 5wt%, 6wt%, 7wt%, etc. can be selected. The number of mixing cycles can be selected as 25, 27, 28, 29, 30, etc., and a high-efficiency stirring mixer can be used for mixing.

[0083] S1.6, main mixing: the third premixed powder, the remaining part of additive B, uranium dioxide and pore-forming agent are mixed for 3 to 5 mixing cycles to obtain a first mixed powder; or the third premixed powder is added in multiple times, firstly, part of the third premixed powder, the remaining part of additive B, uranium dioxide and pore-forming agent are mixed for 3 to 5 mixing cycles, then part of the third premixed powder is added for 3 to 5 mixing cycles, and part of the third premixed powder is repeatedly added and mixed until all the third premixed powder is added, and then mixed for 3 to 5 mixing cycles to obtain a first mixed powder. Among them, the number of mixing cycles can be selected from 3, 4, 5, etc., and a high-efficiency stirring mixer or orbital spiral mixer can be used for mixing.

[0084] In step S1, each mixing cycle includes mixing and cooling. During the mixing process, a large amount of heat will be generated due to the collision and friction between powders and between powders and the inner wall of the mixing container, resulting in an increase in temperature and deterioration of the sintering activity of the powders. Therefore, after a period of mixing, cooling must be performed, that is, mixing first and then cooling, and then entering the next mixing cycle. The sum of the mixing time and cooling time of each mixing cycle is ≤10 minutes, wherein the mixing time is 3 to 5 minutes, and 3min, 3.5min, 4min, 4.5min, 5min, etc. can be selected, and the cooling time is 3 to 5 minutes, and 3min, 3.5min, 4min, 4.5min, 5min, etc. can be selected. If a high-efficiency stirring mixer is used for mixing, the mixing speed is 150-170r / min, and you can choose 150r / min, 155r / min, 160r / min, 165r / min, 170r / min, etc.; the crushing head speed is 2500-3000r / min, and you can choose 2500r / min, 2600r / min, 2700r / min, 2800r / min, 2900r / min, 3000r / min, etc. If an orbital spiral mixer is used for mixing, the screw rod speed is 50-200r / min, and you can choose 50r / min, 100r / min, 125r / min, 150r / min, 200r / min, etc.

[0085] In the premixing of step S1.3 and step S1.5, when the mixed mass of the raw materials is less than 1 kg, a high-energy ball mill can be used for mixing.

[0086] S2, granulation: the first mixture is compressed for the first time and sieved with a sieve, and then a lubricant is added and mixed to obtain a second mixture.

[0087] In step S2, after the first pressing, the density of the first mixture is 4-6 g / cm 3 . The first mixture is pressed into blocks by the first pressing, and the thickness of the blocks is 5 to 15 mm, and the thickness can be selected from 5 mm, 8 mm, 10 mm, 12 mm, 15 mm, etc. The blocks are granulated using a screen (such as a rub screen), and after screening, the first spheroidization is performed for 10 to 15 minutes, preferably 12 to 15 minutes, and 12 minutes, 13 minutes, 14 minutes, 15 minutes, etc. can be selected, and then a lubricant is added and the second spheroidization is performed for 5 to 10 minutes, preferably 8 to 10 minutes, and 8 minutes, 8.5 minutes, 9 minutes, 10 minutes, etc. can be selected. Among them, the aperture of the screen is 1 to 2 mm, and 1 mm, 1.3 mm, 1.5 mm, 2 mm, etc. can be selected. The spheroidization method is to let the mixture particles turn and roll continuously in the double cone mixer.

[0088] S3, molding: the second mixture is pressed for a second time to obtain a green body.

[0089] In step S3, the second mixture is placed in a mold and a hydraulic press is used for a second pressing. The pressing stress of the second pressing is 250-450 MPa, which can be 250 MPa, 300 MPa, 350 MPa, 400 MPa, 450 MPa, etc., preferably 300-400 MPa. The density of the green body is 5.5-6.5 g / cm 3 .

[0090] S4. Sintering: Sinter the green body in a certain sintering atmosphere and sintering temperature to obtain uranium dioxide pellets.

[0091] In step S4, the sintering atmosphere is hydrogen containing up to 5 vol% water vapor or carbon dioxide containing at least 50 vol% nitrogen or argon, wherein the volume percentage of water vapor in hydrogen is preferably 0.5-1.5 vol%, and 0.5 vol%, 0.8 vol%, 1.0 vol%, 1.5 vol%, etc. can be selected; the volume percentage of argon in carbon dioxide is preferably 70-80 vol%, and 70 vol%, 73 vol%, 75 vol%, 80 vol%, etc. can be selected; the volume percentage of nitrogen in carbon dioxide is preferably 60-70 vol%, and 60 vol%, 65 vol%, 68 vol%, 70 vol%, etc. can be selected. The gas flow rate of the sintering atmosphere is 150-250 L / min, the sintering temperature is 1500-1800°C, and the sintering time is 4-12 hours, wherein the gas flow rate can be selected from 150 L / min, 175 L / min, 200 L / min, 225 L / min, 250 L / min, etc., the sintering temperature can be selected from 1500°C, 1600°C, 1700°C, 1800°C, etc., the sintering time can be selected from 4h, 5h, 6h, 8h, 10h, 12h, etc., and the sintering time is preferably 4-6h. The sintering equipment can be a batch furnace or a stepping push boat furnace.

[0092] The present invention adopts a mixing method of staged mixing or "premixing + main mixing" in the preparation process of uranium dioxide pellets, and performs multiple mixing (i.e., multiple mixing cycles), compresses and sieves the mixed raw materials for granulation, then adds a lubricant and mixes them, so that the raw materials are mixed more evenly, and finally performs compression molding and sintering, and densification of the pellets is achieved at a lower sintering temperature and a shorter sintering time, thereby avoiding excessive grain size of the pellets. The preparation method of the present invention improves the plastic deformation capacity of the uranium dioxide pellets, and can effectively reduce the risk of fuel failure caused by the PCI effect. The preparation method of the present invention is suitable for large-scale production, and can be used for laboratory preparation or industrial-grade manufacturing of UO2 pellets of 1 kg / batch to 500 kg / batch.

[0093] The present invention avoids the formation of a second phase in the pellet due to excessive additive dosage, and avoids the weakening of the creep capacity of the pellet due to excessive average grain size of the pellet caused by the pellet composition and preparation process. The production cost, preparation process and quality control of the present invention are comparable to those of commercial UO2 pellets. The present invention can improve the flexible operation capability and high fuel consumption power generation capability of nuclear power plants, and promote the continuous improvement of the economic benefits of nuclear power.

[0094] The following is described by specific examples:

[0095] Example 1

[0096] A uranium dioxide pellet is made of the following raw materials in percentage by mass: 0.1wt% of pore former, 0.1wt% of lubricant, 0.1wt% of additive A, 12wt% of additive B, and the remainder is uranium dioxide. Additive A is Cr2O3, additive B is U3O8, the pore former is ammonium oxalate, and the lubricant is aker wax.

[0097] A method for preparing the above-mentioned uranium dioxide pellets comprises the following steps:

[0098] S1. Mixing: Using pore former, lubricant, additive A, additive B and uranium dioxide as raw materials, the pore former, additive A, additive B and uranium dioxide are mixed to obtain a first mixture. The mass percentages of the raw materials meet the following conditions: pore former 0.1wt%, lubricant 0.1wt%, additive A 0.1wt%, additive B 12wt%, and the remainder is uranium dioxide. Additive A is Cr2O3, additive B is U3O8, the pore former is ammonium oxalate, and the lubricant is acryl wax.

[0099] The mixing step adopts the first implementation mode, and step S1 includes the following sub-steps:

[0100] S1.1, first stage mixing: the pore former, additive A, additive B and uranium dioxide are mixed for a total of 12 mixing cycles to obtain a first premixed powder.

[0101] S1.2, two-stage mixing: the first premixed powder is mixed for a total of 28 mixing cycles to obtain a first mixture.

[0102] In step S1, a high-efficiency stirring mixer is used for mixing. The mixing time of each mixing cycle is 4 minutes, the cooling time is 4 minutes, the mixing speed is 160 r / min, and the crushing head speed is 2800 r / min.

[0103] S2, granulation: the first mixture is compressed for the first time and sieved with a sieve, and then a lubricant is added and mixed to obtain a second mixture.

[0104] In step S2, the first mixture is pressed into a block by the first pressing, and the thickness of the block is 10 mm and the density is 4.8 g / cm 3 The briquette was granulated using a screen, and after screening, the first spheroidization was performed for 12 minutes, followed by the addition of a lubricant and the second spheroidization for 8 minutes, wherein the aperture of the screen was 1.5 mm.

[0105] S3, molding: the second mixture is pressed for a second time to obtain a green body.

[0106] In step S3, the second mixture is placed in a mold and pressed for the second time using a hydraulic press. The pressing stress of the second pressing is 350 MPa, and the density of the green body is 6.0 g / cm 3 .

[0107] S4. Sintering: Sinter the green body in a certain sintering atmosphere and sintering temperature to obtain uranium dioxide pellets.

[0108] In step S4, sintering is performed in an atmospheric pressure sintering furnace, the sintering atmosphere is hydrogen containing 1.0 vol% water vapor, the gas flow rate of the sintering atmosphere is 200 L / min, the sintering temperature is 1700° C., and the sintering time is 5 hours.

[0109] Example 2

[0110] A uranium dioxide pellet is made of the following raw materials in percentage by mass: 0.13wt% of a pore former, 0.2wt% of a lubricant, 0.04wt% of an additive A, 13wt% of an additive B, and the remainder is uranium dioxide. Additive A is TiO2, additive B is U3O8, the pore former is ammonium oxalate, and the lubricant is zinc stearate.

[0111] A method for preparing the above-mentioned uranium dioxide pellets comprises the following steps:

[0112] S1. Mixing: Using pore former, lubricant, additive A, additive B and uranium dioxide as raw materials, the pore former, additive A, additive B and uranium dioxide are mixed to obtain a first mixture. The mass percentages of the raw materials meet the following conditions: pore former 0.13wt%, lubricant 0.2wt%, additive A 0.04wt%, additive B 13wt%, and the remainder is uranium dioxide. Additive A is TiO2, additive B is U3O8, the pore former is ammonium oxalate, and the lubricant is zinc stearate.

[0113] The mixing step adopts the second implementation mode, and step S1 includes the following sub-steps:

[0114] S1.3, premixing: uranium dioxide is added in two portions, and part of the uranium dioxide (accounting for 22 wt% of the total uranium dioxide) is mixed with additive A for a total of 25 mixing cycles to obtain a second premixed powder.

[0115] S1.4, main mixing: the second premixed powder, additive B, the remaining uranium dioxide and the pore-forming agent are mixed for a total of 25 mixing cycles to obtain a first mixture.

[0116] In step S1, a high-efficiency stirring mixer is used for mixing. The mixing time of each mixing cycle is 3 minutes, the cooling time is 3 minutes, the mixing speed is 170 r / min, and the crushing head speed is 3000 r / min.

[0117] S2, granulation: the first mixture is compressed for the first time and sieved with a sieve, and then a lubricant is added and mixed to obtain a second mixture.

[0118] In step S2, the first mixture is pressed into a block by the first pressing, and the thickness of the block is 5 mm and the density is 6 g / cm 3 The briquette was granulated using a screen, and after screening, the first spheroidization was performed for 13 minutes, followed by the addition of a lubricant and the second spheroidization for 9 minutes, wherein the aperture of the screen was 2 mm.

[0119] S3, molding: the second mixture is pressed for a second time to obtain a green body.

[0120] In step S3, the second mixture is placed in a mold and pressed for a second time using a hydraulic press. The pressing stress of the second pressing is 250 MPa, and the density of the green body is 5.5 g / cm 3 .

[0121] S4. Sintering: Sinter the green body in a certain sintering atmosphere and sintering temperature to obtain uranium dioxide pellets.

[0122] In step S4, sintering is performed in an atmospheric pressure sintering furnace, the sintering atmosphere is carbon dioxide containing 75 vol% argon, the gas flow rate of the sintering atmosphere is 150 L / min, the sintering temperature is 1600° C., and the sintering time is 6 hours.

[0123] Example 3

[0124] A uranium dioxide pellet is made of the following raw materials in percentage by mass: 0.15wt% of pore former, 0.3wt% of lubricant, 0.06wt% of additive A, 15wt% of additive B, and the remainder is uranium dioxide. Additive A is 0.03wt% Cr2O3+0.03wt% Mn2O3, additive B is U3O8, the pore former is ammonium oxalate, and the lubricant is lithium stearate.

[0125] A method for preparing the above-mentioned uranium dioxide pellets comprises the following steps:

[0126] S1. Mixing: Using pore former, lubricant, additive A, additive B and uranium dioxide as raw materials, the pore former, additive A, additive B and uranium dioxide are mixed to obtain a first mixture. The mass percentages of the raw materials meet the following conditions: pore former 0.15wt%, lubricant 0.3wt%, additive A 0.06wt%, additive B 15wt%, and the remainder is uranium dioxide. Additive A is 0.03wt% Cr2O3+0.03wt% Mn2O3, additive B is U3O8, the pore former is ammonium oxalate, and the lubricant is lithium stearate.

[0127] The mixing step adopts the second implementation mode, and step S1 includes the following sub-steps:

[0128] S1.3, premixing: uranium dioxide is added in two portions, and part of the uranium dioxide (accounting for 33 wt% of the total uranium dioxide) is mixed with additive A for a total of 30 mixing cycles to obtain a second premixed powder.

[0129] S1.4, main mixing: the second premixed powder, additive B, the remaining uranium dioxide and the pore-forming agent are mixed for a total of 30 mixing cycles to obtain a first mixture.

[0130] In step S1, a high-efficiency stirring mixer is used for mixing. The mixing time of each mixing cycle is 5 minutes, the cooling time is 5 minutes, the mixing speed is 150 r / min, and the crushing head speed is 2500 r / min.

[0131] S2, granulation: the first mixture is compressed for the first time and sieved with a sieve, and then a lubricant is added and mixed to obtain a second mixture.

[0132] In step S2, the first mixture is pressed into a block by the first pressing, and the block has a thickness of 5 mm and a density of 5 g / cm 3 The briquette was granulated using a screen, and after screening, the first spheroidization was performed for 14 minutes, followed by the addition of a lubricant and the second spheroidization for 10 minutes, wherein the aperture of the screen was 2 mm.

[0133] S3, molding: the second mixture is pressed for a second time to obtain a green body.

[0134] In step S3, the second mixture is placed in a mold and pressed for a second time using a hydraulic press. The pressing stress of the second pressing is 300 MPa, and the density of the green body is 5.8 g / cm 3 .

[0135] S4. Sintering: Sinter the green body in a certain sintering atmosphere and sintering temperature to obtain uranium dioxide pellets.

[0136] In step S4, sintering is performed in an atmospheric pressure sintering furnace, the sintering atmosphere is carbon dioxide containing 80 vol% argon, the gas flow rate of the sintering atmosphere is 250 L / min, the sintering temperature is 1700° C., and the sintering time is 4 hours.

[0137] Example 4

[0138] A uranium dioxide pellet is made of the following raw materials in percentage by weight: 0.14wt% of pore former, 0.2wt% of lubricant, 0.07wt% of additive A, 14wt% of additive B, and the remainder is uranium dioxide. Additive A is 0.03wt% TiO2+0.04wt% V2O5, additive B is U3O8, the pore former is ammonium oxalate, and the lubricant is calcium stearate.

[0139] A method for preparing the above-mentioned uranium dioxide pellets comprises the following steps:

[0140] S1. Mixing: Using pore former, lubricant, additive A, additive B and uranium dioxide as raw materials, the pore former, additive A, additive B and uranium dioxide are mixed to obtain a first mixture. The mass percentages of the raw materials meet the following conditions: pore former 0.14wt%, lubricant 0.2wt%, additive A 0.07wt%, additive B 14wt%, and the remainder is uranium dioxide. Additive A is 0.03wt% TiO2+0.04wt% V2O5, additive B is U3O8, the pore former is ammonium oxalate, and the lubricant is calcium stearate.

[0141] The mixing step adopts the third implementation mode, and step S1 includes the following sub-steps:

[0142] S1.5, premixing: Additive B is added twice, and additive A and part of additive B (accounting for 5wt% of the raw material) are mixed for a total of 26 mixing cycles, and a high-efficiency stirring mixer is used to mix to obtain a third premixed powder. The mixing time of each mixing cycle is 4.5 minutes, the cooling time is 4.5 minutes, the mixing speed is 155r / min, and the crushing head speed is 2600r / min.

[0143] S1.6, main mixing: the third premixed powder is added in multiple times, firstly, part of the third premixed powder, the remaining part of additive B, uranium dioxide and pore-forming agent are mixed for 5 mixing cycles, then part of the third premixed powder is added for 5 mixing cycles, and part of the third premixed powder is added and mixed repeatedly until all the third premixed powder is added, and then mixed for 5 mixing cycles to obtain the first mixed powder. The main mixing step is mixed by an orbital screw mixer, and the mixing time for each mixing cycle is 5 minutes, the cooling time is 5 minutes, and the screw speed is 100r / min.

[0144] S2, granulation: the first mixture is compressed for the first time and sieved with a sieve, and then a lubricant is added and mixed to obtain a second mixture.

[0145] In step S2, the first mixture is pressed into a block by the first pressing, and the thickness of the block is 12 mm and the density is 5.5 g / cm 3 The briquette was granulated using a screen, and after screening, the first spheroidization was performed for 13 minutes, followed by the addition of a lubricant and the second spheroidization for 10 minutes, wherein the aperture of the screen was 1.5 mm.

[0146] S3, molding: the second mixture is pressed for a second time to obtain a green body.

[0147] In step S3, the second mixture is placed in a mold and pressed for a second time using a hydraulic press. The pressing stress of the second pressing is 400 MPa, and the density of the green body is 6.5 g / cm 3 .

[0148] S4. Sintering: Sinter the green body in a certain sintering atmosphere and sintering temperature to obtain uranium dioxide pellets.

[0149] In step S4, the sintering atmosphere is carbon dioxide containing 65 vol% nitrogen, the gas flow rate of the sintering atmosphere is 250 L / min, and the sintering is carried out in an atmosphere step-type push-boat sintering furnace, moving one step every 40 to 60 minutes, the preheating zone moves two steps, the pre-sintering temperatures are 500±50°C and 750±50°C, the sintering zone moves four steps, the sintering temperature range is 1500-1600°C, and the total sintering time is 6 hours.

[0150] Comparative test:

[0151] The uranium dioxide pellets prepared in Example 1 of the present invention were compared with commercial uranium dioxide pellets, wherein the commercial UO2 pellets, i.e., ordinary UO2 pellets prepared by conventional processes, were made by pressing uranium dioxide mixed with pore-forming agents and lubricants into green compacts, and then sintering them at 1700-1800°C in hydrogen for 6-8 hours. The UO2 pellets of Example 1 and the commercial UO2 pellets were subjected to power transient tests in a test reactor using irradiated small rod elements, and the anti-PCI performance (i.e., high-temperature plastic deformation capability) of the UO2 pellets was tested by increasing the power step. The test results are as follows: Figures 1 to 4 As shown. The power transient means that the power of the fuel and the reactor is in an unstable state (continuously changing state). The power transient test method belongs to the prior art. This test method mainly achieves a short-term increase in nuclear reaction power by suddenly changing the position of the power control rod or suddenly removing the gaseous neutron absorber.

[0152] The UO2 core block has a dish-shaped (shallow dish-shaped depression) end face. Butterfly filling refers to the fact that the dish-shaped end face is filled and disappears due to the expansion and plastic flow of the material in the center of the core block. Figure 1 , Figure 2 The UO2 pellets of Example 1 of the present invention and the commercial UO2 pellets at high temperatures are shown. It can be seen that under the same test conditions, the disc-shaped end face of the UO2 pellet of the present invention disappears and disc-shaped filling occurs, indicating that the pellet has stronger plastic flow and can relieve the contact stress between the pellet and the cladding; while the disc-shaped end face of the commercial UO2 pellet is retained, no disc-shaped filling occurs, the pellet has obvious cracks, and there is cladding damage, indicating that the pellet has low plastic flow. Therefore, the UO2 pellet of the present invention has high-temperature plasticity, that is, it has adjustable deformation capacity when subjected to compressive stress at high temperature.

[0153] Figure 3 , Figure 4 They are respectively the UO2 pellets of Example 1 of the present invention and the commercial UO2 pellets after power transient. It can be seen that the cladding loaded with the UO2 pellets of the present invention is intact, and there are no through cracks in both the pellets and the cladding, while the cladding loaded with the commercial UO2 pellets is obviously damaged.

[0154] The temperature distribution of the UO2 pellet is high in the center and low at the edge, so the thermal expansion of the centerline area of ​​the UO2 pellet is most significant. Since the UO2 pellet of the present invention has a strong plastic deformation ability, in the process of power increase (temperature increase), the material in the centerline area of ​​the pellet will quickly complete plastic deformation (plastic flow), and the shape change of the pellet is manifested as the disappearance and filling of the dish-shaped end face. Since the plastic deformation of the pellet absorbs a large amount of mechanical energy, the stress generated by the contact between the pellet and the cladding is greatly reduced, so that the risk of the cladding being damaged is alleviated. It can be seen that the UO2 pellet of the present invention has a good plastic deformation ability, and the deformation energy absorption is obvious at high temperature, which can alleviate the fuel damage caused by the cladding-pellet interaction (PCI).

[0155] It can be understood that the above embodiments only express the preferred implementation modes of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the patent scope of the present invention. It should be pointed out that, for ordinary technicians in this field, without departing from the concept of the present invention, the above technical features can be freely combined, and several deformations and improvements can be made, which all belong to the protection scope of the present invention. Therefore, all equivalent changes and modifications made to the scope of the claims of the present invention should belong to the scope covered by the claims of the present invention.

Claims

1. A uranium dioxide pellet, characterized in that: The invention is prepared from the following raw materials in percentage by weight: 0.1-0.3 wt% of a pore former, 0.1-0.3 wt% of a lubricant, 0.03-0.15 wt% of an additive A, 12-15 wt% of an additive B, and the balance is uranium dioxide; the additive A comprises at least one metal oxide, the metal element in the metal oxide is an element of group IVB, group VB, group VIB or group VIIB, and the additive B is triuranium octoxide.

2. The uranium dioxide pellet according to claim 1, characterized in that: The pore-forming agent is ammonium oxalate; and / or the lubricant is aker wax or stearate.

3. The uranium dioxide pellet according to claim 1, characterized in that: The cation radius of the metal element in the metal oxide is U 4+ The radius of the ion is at least 30% smaller, and the equivalent boron content of the metal element is less than 0.004 μg / gU.

4. A method for preparing uranium dioxide pellets according to claim 1, characterized in that: The following steps are involved: S1, mixing: using a pore former, a lubricant, an additive A, an additive B and uranium dioxide as raw materials, mixing the pore former, the additive A, the additive B and the uranium dioxide to obtain a first mixture; the mass percentages of the raw materials satisfy: pore former 0.1-0.3wt%, lubricant 0.1-0.3wt%, additive A 0.03-0.15wt%, additive B 12-15wt%, and the balance is uranium dioxide; S2, granulation: the first mixture is compressed for the first time and sieved with a sieve, and then the lubricant is added and mixed to obtain a second mixture; S3, molding: pressing the second mixture for a second time to obtain a green body; S4, sintering: sintering the green body in a certain sintering atmosphere and at a certain sintering temperature to obtain a uranium dioxide pellet.

5. The method for preparing uranium dioxide pellets according to claim 4, characterized in that: The S1 step includes the following sub-steps: S1.1, first-stage mixing: mixing the pore-forming agent, the additive A, the additive B and the uranium dioxide for 10 to 13 mixing cycles to obtain a first premixed powder; S1.2, two-stage mixing: the first premixed powder is mixed for 25 to 30 mixing cycles to obtain the first mixture.

6. The method for preparing uranium dioxide pellets according to claim 4, characterized in that: The S1 step includes the following sub-steps: S1.3, premixing: the uranium dioxide is added twice, and part of the uranium dioxide and the additive A are mixed for a total of 25 to 30 mixing cycles to obtain a second premixed powder; S1.4, main mixing: the second premixed powder, the additive B, the remaining part of the uranium dioxide and the pore-forming agent are mixed for a total of 25 to 30 mixing cycles to obtain the first mixture.

7. The method for preparing uranium dioxide pellets according to claim 4, characterized in that: The S1 step includes the following sub-steps: S1.5, premixing: the additive B is added twice, and the additive A and part of the additive B are mixed for a total of 25 to 30 mixing cycles to obtain a third premixed powder; S1.6, main mixing: the third premixed powder, the remaining part of the additive B, the uranium dioxide and the pore-forming agent are mixed for a total of 3 to 5 mixing cycles to obtain a first mixed powder; or, the third premixed powder is added in multiple times, firstly, part of the third premixed powder, the remaining part of the additive B, the uranium dioxide and the pore-forming agent are mixed for 3 to 5 mixing cycles, and then part of the third premixed powder is added and mixed for 3 to 5 mixing cycles, and part of the third premixed powder is added and mixed repeatedly until all the third premixed powder is added, and then mixed for 3 to 5 mixing cycles to obtain a first mixed powder.

8. The method for preparing uranium dioxide pellets according to any one of claims 5 to 7, characterized in that: In the step S1, each mixing cycle includes mixing and cooling, the sum of the mixing time and the cooling time of each mixing cycle is ≤10 minutes, and the mixing speed is 50-200 r / min.

9. The method for preparing uranium dioxide pellets according to claim 4, characterized in that: In the step S2, after the first mixture is pressed for the first time, the density is 4 to 6 g / cm 3 ; After sieving through a sieve, the first spheroidization is performed for 10 to 15 minutes, and then the lubricant is added and the second spheroidization is performed for 5 to 10 minutes, and the aperture of the sieve is 1 to 2 mm; In the step S3, the pressing stress of the second pressing is 250-450 MPa, and the density of the green body is 5.5-6.5 g / cm 3 .

10. The method for preparing uranium dioxide pellets according to claim 4, characterized in that: In the S4 step, the sintering atmosphere is hydrogen containing up to 5 vol% water vapor or carbon dioxide containing at least 50 vol% nitrogen or argon, the gas flow rate of the sintering atmosphere is 150-250 L / min, the sintering temperature is 1500-1800°C, and the sintering time is 4-12 hours.

Citation Information

Cited By

  • Batch manufacturing method of large-grain uranium dioxide pellets and uranium dioxide pellets

    CN121405437A